2019
DOI: 10.4014/jmb.1901.01015
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of Novel and Bioactive Metabolites from Endophytic Fungi Isolated from Rubber Tree Ficus elastica Leaves

Abstract: Endophytic fungi are an important component of plant microbiota, and have the excellent capacity for producing a broad variety of bioactive metabolites. These bioactive metabolites not only affect the survival of the host plant, but also provide valuable lead compounds for novel drug discovery. In this study, forty-two endophytic filamentous fungi were isolated from Ficus elastica leaves, and further identified as seven individual taxa by ITS-rDNA sequencing. The antimicrobial activity of these endophytic fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Fungal genomic DNA was isolated using the CTAB method [ 25 ]. The oligonucleotide sequences of PCR primers are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal genomic DNA was isolated using the CTAB method [ 25 ]. The oligonucleotide sequences of PCR primers are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the application of this regulation technique is limited to endophytic fungi. In this study, we constructed an hdaA homologue deletion mutant of P. chrysogenum Fes1701, an endophytic fungus isolated from rubber tree ( Ficus elastica ) leaves [ 25 ], and investigated the effects of HdaA inactivation on secondary metabolism. Our results indicate that the ΔhdaA strain showed a significant change of secondary metabolic profile with the emergence of some SMs.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial potential of 237 and 238 separated Trichoderma harzianum was investigated towards B. subtilis, E. coil, C. albicans, S. aureus, and P. aeruginosa using well diffusion technique. They had a weak inhibitory effect against E. coli (MICs 32 µg/mL), compared to chloramphenicol (MIC 4 µg/mL), whereas they were inactive towards the other tested microorganisms [69]. Compounds [73].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) values of the pure compounds were evaluated by dilution in EtOH to obtain series concentrations of 256,128,64,32,16,8, and 4 μg/mL. The inhibition zone > 9 mm indicated that the compound had antibacterial activity at the corresponding concentration (Ding et al 2019).…”
Section: Antibacterial Activity Of Cordyline Fruticosa Leaf Extracts mentioning
confidence: 99%
“…Endophytic fungi obtain nutrients, protection, and growing sites from host plants. Several endophytic fungal species have been reported to produce antibacterial, antifungal, antiviral, anti-inflammatory, and antitumor bioactive compounds that can protect host plants (Hussain et al 2014;Bungtongdee et al 2018;Praptiwi et al 2018;Ding et al 2019).…”
Section: Introductionmentioning
confidence: 99%